Essential Oil-Induced Downregulation of Aflatoxin Biosynthetic Genes in Aspergillus Flavus: A Natural Strategy for Reducing Crop Contamination - Intesar Ali Mezeal (Jurnal MIPA dan Pembelajarannya, 2026)
Background: Aspergillus flavus is an important aflatoxigenic fungus associated with contamination of maize, wheat, peanuts and other stored crops. Aflatoxin B1 (AFB1) is a highly toxic and carcinogenic secondary metabolite, and its biosynthesis is controlled by clustered structural and regulatory genes, including aflR, aflS, aflD, aflM, aflP and aflQ. Objective: This study evaluated the inhibitory effects of cinnamon, clove and thyme essential oils on A. flavus growth, AFB1 production and relative expression of selected aflatoxin biosynthetic genes under controlled in vitro conditions. Methods: An aflatoxigenic A. flavus isolate was exposed to essential oils at 0.25, 0.50 and 1.00 µL/mL. Radial growth inhibition was determined on potato dextrose agar, while mycelial dry weight and AFB1 production were evaluated in yeast extract sucrose broth. AFB1 was quantified by HPLC with fluorescence detection. Relative expression of aflR, aflS, aflD, aflM, aflP and aflQ was determined by RT-qPCR using β-tubulin as the reference gene and the 2^-ΔΔCt method. Results: The results showed a concentration-dependent decrease in fungal growth, biomass and AFB1 production. Cinnamon oil produced the strongest inhibition, reducing radial growth by 54.3% and AFB1 production by 81.7% at 1.00 µL/mL. Clove oil reduced AFB1 by 73.4%, whereas thyme oil reduced it by 65.2% at the same concentration. RT-qPCR analysis showed downregulation of all tested biosynthetic genes, with aflR and aflD showing the most consistent suppression. Cinnamon oil reduced aflR expression to 0.24-fold and aflD expression to 0.19-fold compared with the untreated control. Conclusion: The findings demonstrate that essential oils, particularly cinnamon and clove oils, reduced AFB1 production through both growth inhibition and transcriptional suppression of key aflatoxin biosynthetic genes. These results support the use of plant-derived essential oils as natural anti-aflatoxigenic agents in strategies aimed at reducing crop contamination.